Binder as well as preparation method and application thereof
By using a specific composition of adhesive, the problem of shear viscosity and viscosity recovery time of the battery paste during coating is solved, and the quality of the electrode sheet and the comprehensive performance of the battery are improved.
Patent Information
- Application Number
- CN202411916142.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-24
AI Technical Summary
The shear viscosity of the existing battery paste is not suitable during the coating process, resulting in poor coating and inappropriate viscosity recovery time, which affects the edge flatness and thickness consistency of the electrode sheet.
A binder consisting of the first monomer, the second monomer, the third monomer and the fourth monomer are used to form a polymer with specific rheological characteristics through the combined reaction of these monomers, ensuring that the electrode slurry is smoothly coated at high shear rates, and gradually increasing the viscosity during the advection process to return to a higher level.
The rheological characteristics of the electrode slurry are improved, the coating processing performance is improved, and the electrode plate edges formed are high flatness and quality are improved, so that batteries with excellent comprehensive performance can be obtained.
Smart Images

Figure BDA0005206863620000101 
Figure BDA0005206863620000111 
Figure BDA0005206863620000112
Abstract
Description
Technical Field
[0001] The present application relates to the field of batteries, and in particular to a binder and a preparation method and application thereof. Background Art
[0002] Battery slurry is crucial to the preparation and processing of battery pole pieces and is a key factor in determining the quality of battery pole pieces. Battery slurry is a high-viscosity solid-liquid two-phase suspension system obtained by stirring and fully dispersing active materials, binders, conductive agents and other materials in a solvent, and then coating the battery slurry on the surface of the current collector to obtain a battery pole piece.
[0003] The coating of battery slurry is a process involving different shear rates. In the stage of coating the battery slurry on the current collector, the electrode slurry needs to undergo a high shear rate. At this time, the shear viscosity of the electrode slurry should not be too high to avoid uneven coating. After the electrode slurry is coated on the current collector, the electrode slurry enters the advection stage under the action of gravity and surface tension on the current collector. At this time, the shear rate is low; in order to ensure that the coating surface is smooth and the thickness is consistent, the viscosity of the electrode slurry needs to gradually increase during the advection process and recover to a higher level. At the same time, the recovery time of the battery slurry viscosity during the advection process should be neither too long nor too short. If the recovery time is too long, the fluidity of the slurry during the advection process is too high, which may cause tailing at the edge of the coating, or the lower edge is thicker than the coating above it, resulting in excessive local voltage of the battery cell; if the recovery time is too short, the electrode slurry cannot be fully leveled, resulting in uneven coating, uneven pressure distribution of the electrode plate during the compaction process, and uneven porosity, thereby affecting the capacity of the battery cell.
[0004] Therefore, controlling the rheological properties of electrode slurry is crucial to obtain high-quality battery electrodes.
[0005] As the most important polymer material in battery slurry, binder plays a key role in battery slurry. Its performance directly affects the rheological properties of battery slurry, and then affects the manufacturing quality and final performance of battery cells. Therefore, it is crucial to develop a binder that can improve the rheological properties of battery slurry and then improve the preparation quality of battery pole sheets, so as to obtain battery cells with excellent performance. Summary of the invention
[0006] In view of the above problems, the present application provides a binder and a preparation method and application thereof. The binder not only has excellent bonding properties, but also improves the rheological properties of the electrode slurry formed thereby, and improves the coating and processing performance of the electrode slurry. Furthermore, the edge flatness of the electrode plate formed thereby is high. The binder improves the quality of the electrode plate, and a battery with excellent comprehensive performance can be obtained.
[0007] In a first aspect, the present application provides a binder, wherein raw materials for preparing the binder include a first monomer, a second monomer, a third monomer, and a fourth monomer;
[0008] The first monomer includes a cyclic anhydride compound and / or a non-carboxyl polyamine;
[0009] The second monomer includes a small molecule carboxyl polyamine;
[0010] The third monomer includes a polymer polyamine and / or a polymer polyol;
[0011] The fourth monomer includes isocyanate.
[0012] In the technical scheme of the embodiment of the present application, the fourth monomer is used as the reaction matrix in the binder, and three different monomers are matched. In the formed binder, some polymer segments have certain intramolecular or intermolecular forces, so that the segments are easy to form a relatively neat and regular ordered phase, thereby obtaining a polymer with certain rheological properties. The electrode slurry formed by the above-mentioned binder undergoes a high shear rate in the coating stage. At this time, under the action of shear force, the polymer is unwound, and the interaction between the polymer chain and the polymer chain is small. The shear viscosity of the electrode slurry is in a relatively low range, so that the slurry can be smoothly coated on the current collector; after the electrode slurry is coated on the current collector, the slurry is in the advection stage, and the shear rate decreases rapidly. At this time, the interaction between the polymer chain and the polymer chain gradually increases, and the neat and regular segments in the polymer are partially restored and formed. The viscosity of the electrode slurry gradually increases with the advection process, and recovers to a higher level within a suitable time range, so that the thickness of the formed coating is uniform and the edge flatness is high. Combined with the excellent bonding performance of the binder, the quality of the electrode plate is further improved, thereby obtaining a battery with excellent comprehensive performance.
[0013] Specifically, the first monomer, as a basic monomer that reacts with the fourth monomer, forms the main chain skeleton of the binder; the second monomer contains a strong polar carboxyl group, which can make the polymer form a certain strength of intra-chain or inter-chain interaction force, adjust the rheological properties of the binder, and improve the bonding strength of the binder through the interaction between the carboxyl group and the metal current collector; the third monomer can form a neat and regular polymer segment, which can be transformed from a curled state to an extended state under high shear; after the external force on the slurry is removed, that is, when it is transformed into low shear, the segment can be restored from an extended state to a curled state within a certain period of time, thereby strengthening the rheological properties of the binder. Therefore, the four monomers cooperate with each other and work synergistically, so that the binder has excellent bonding properties and improves the rheological properties of the binder, which is beneficial to its application in batteries.
[0014] In the present application, small molecule carboxyl polyamine refers to a carboxyl polyamine that does not contain a polymer segment, and its molecular weight depends on the chemical formula of the polyamine.
[0015] Preferably, the cyclic acid anhydride compound includes 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,3,3',4'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride, 2,3,3',4'-diphenyl ether tetracarboxylic dianhydride, 4,4'-(4,4'-isopropyldiphenoxy)bis(phthalic anhydride), 3,3',4,4'-diphenyl sulfone tetracarboxylic dianhydride, Any one of or a combination of at least two of the following: 1,2,4-cyclohexanetricarboxylic anhydride, 1,4,5,8-naphthalenetetracarboxylic anhydride, 1,2,3,4-cyclobutanetetracarboxylic anhydride, and bicyclo(2.2.2)oct-7-ene-2,3,5,6-tetracarboxylic anhydride.
[0016] Preferably, the cyclic anhydride compound includes any one of 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride, 2,3,3',4'-diphenyl ether tetracarboxylic dianhydride or 4,4'-(4,4'-isopropyldiphenoxy)bis(phthalic anhydride) or a combination of at least two thereof.
[0017] Preferably, the number of amino groups in the non-carboxyl polyamine is ≥ 2, such as 3, 4, etc. Optionally, the non-carboxyl polyamine includes a non-carboxyl diamine.
[0018] Preferably, the non-carboxyl polyamine includes p-phenylenediamine, m-phenylenediamine, 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 4,4'-diaminobenzophenone, 2,7-diamino-9-fluorenone, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminodiphenyl sulfone, 4,4'-diaminobiphenyl, 4,4'-diaminodiphenylmethane, 1,4-bis(4'-aminophenoxy)benzene, 1,3-bis(4'-aminophenoxy)benzene, 2,2- Any one of bis[4-(4-aminophenoxy)phenyl]propane, 2,2'-bis(trifluoromethyl)diaminobiphenyl, 5-amino-2-(4-aminophenyl)benzimidazole, 1,2-bis(2-aminoethoxy)ethane, 3,6,9-trioxaundecane-1,11-diamine, 3,6,9,12-tetraoxatetradecane-1,14-diamine, polyoxyethylene diamine, and 1,3-bis(3-aminopropyl)tetramethyldisiloxane, or a combination of at least two thereof.
[0019] Preferably, the non-carboxyl polyamine includes one or a combination of two or more of 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 1,4-bis(4'-aminophenoxy)benzene, 1,3-bis(4'-aminophenoxy)benzene, 2,2-bis[4-(4-aminophenoxy)benzene]propane, 1,2-bis(2-aminoethoxy)ethane, 3,6,9-trioxaundecane-1,11-diamine, 3,6,9,12-tetraoxatetradecane-1,14-diamine, polyoxyethylene diamine, and 1,3-bis(3-aminopropyl)tetramethyldisiloxane.
[0020] Preferably, the number of amino groups in the small molecule carboxyl polyamine is ≥ 2, such as 3, 4, etc. Optionally, the small molecule carboxyl polyamine includes a small molecule carboxyl diamine.
[0021] Preferably, the small molecule carboxyl polyamine includes lysine, hydroxylysine, arginine, histidine, 2,5-diaminocyclohexanecarboxylic acid, 3,5-diaminocyclohexanecarboxylic acid, 2,4-diaminobenzoic acid, 2,5-diaminobenzoic acid, 3,5-diaminobenzoic acid, 4,6-diamino-1,3-phthalic acid, 2,5-diamino-1,4-phthalic acid, 4,4'-diaminobiphenyl-3-carboxylic acid, 4,4'-diaminobiphenyl-3,3'-dicarboxylic acid, 4,4'-diaminobiphenyl-2,2'-dicarboxylic acid, 3,3'-diaminobiphenyl-4,4'-dicarboxylic acid, 3,3'-diaminobiphenyl-2,4'-dicarboxylic acid, 4,4'-diamino-3,3'-dicarboxy-5,5'-dimethylbiphenyl, 4,4'-diamino-3,3'-dicarboxylic acid Any one or a combination of at least two of -5,5'-dimethoxybiphenyl, 4,4'-diaminodiphenylmethane-3-carboxylic acid, 4,4'-diaminodiphenylmethane-3,3'-dicarboxylic acid, 4,4'-diaminodiphenylethane-3-carboxylic acid, 4,4'-diaminodiphenylethane-3,3'-dicarboxylic acid, bis(4-amino-3-carboxyphenyl) ether, bis(4-amino-3,5-dicarboxyphenyl) ether, 1,4-bis(4-amino-3-carboxyphenoxy)benzene, 1,3-bis(4-amino-3-carboxyphenoxy)benzene, bis(4-amino-3-carboxyphenyl) sulfone, bis(4-amino-3,5-dicarboxyphenyl) sulfone, bis[4-(4-amino-3-carboxyphenoxy)phenyl]sulfone, and bis[4-(4-amino-3-carboxyphenoxy)phenyl]propane.
[0022] Preferably, the number average molecular weight of the third monomer is ≤3000 g / mol, for example, 500 g / mol, 1000 g / mol, 1500 g / mol, 2000 g / mol, 2500 g / mol, etc.
[0023] In the technical solution of the implementation mode of the present application, the number average molecular weight of the third monomer is within the above range. If the molecular weight of the third monomer is too large, the proportion of neat and regular polymer chain segments increases. Under high shear, the energy barrier required for the polymer molecular chain to transform from a curled state to a stretched state gradually increases, thereby increasing the thixotropic time and weakening the rheological properties.
[0024] Preferably, the number of amino groups in the polymer polyamine is ≥2, such as 3, 4, etc. Optionally, the polymer polyamine includes a polymer diamine.
[0025] Preferably, the polymer polyamine includes any one of polyamide polyamine, polyester polyamine, polyesteramide polyamine or polyacetal polyamine, or a combination of at least two thereof.
[0026] Preferably, the polymer diamine includes any one of polyamide diamine, polyester diamine, polyester amide diamine or polyacetal diamine, or a combination of at least two thereof.
[0027] Preferably, the number of hydroxyl groups in the polymer polyol is ≥2, such as 3, 4, etc. Optionally, the polymer polyol includes a polymer diol.
[0028] Preferably, the polymer polyol includes any one of polyamide polyol, polyester polyol, polyesteramide polyol or polyacetal polyol, or a combination of at least two thereof.
[0029] Preferably, the polymer diol includes any one of polyamide diol, polyester diol, polyesteramide diol or polyacetal diol, or a combination of at least two thereof.
[0030] In the present application, the polyamide polyamine / alcohol, polyester polyamine / alcohol, polyesteramide polyamine / alcohol are prepared by reacting saturated / unsaturated polycarboxylic acids with saturated / unsaturated polyols, saturated / unsaturated polyamines or amino alcohols, and can also be prepared by ring-opening polymerization of lactones or lactams.
[0031] In the present application, the polyacetal polyamine / alcohol is prepared by reacting formaldehyde with saturated / unsaturated polyols, polyamines or amino alcohols.
[0032] In the present application, the saturated or unsaturated polycarboxylic acid includes one or more of succinic acid, glutaric acid, adipic acid, tartaric acid, citric acid, terephthalic acid, phthalic acid or maleic acid.
[0033] In the present application, the saturated or unsaturated polyol includes one or more of ethylene glycol, 1,2-propylene glycol, 1,4-butylene glycol, 1,4-butene glycol, 1,5-pentanediol, neopentyl glycol, hexanediol, diethylene glycol or trimethylolpropane.
[0034] In the present application, the saturated / unsaturated polyamine includes one or more of ethylenediamine, 1,4-butylenediamine, cyclohexanediamine, 1,6-hexanediamine, decanediamine, diethylenetriamine, triethylenetetramine or polyethylenepolyamine.
[0035] In the present application, the amino alcohol includes one or more of ethanolamine, butanolamine, 6-amino-1-hexanol or 4-aminocyclohexanol.
[0036] Preferably, based on 100 parts by weight of the total weight of the first monomer, the second monomer and the third monomer, the weight of the first monomer is 20 to 40 parts, for example, 25 parts, 30 parts, 35 parts, etc.; and / or;
[0037] The weight proportion of the second monomer is 10 to 30 parts, such as 15 parts, 20 parts, 25 parts, etc.; and / or;
[0038] The weight proportion of the third monomer is 30 to 70 parts, for example, 35 parts, 40 parts, 45 parts, 50 parts, 55 parts, 60 parts, 65 parts, etc.
[0039] In the technical solution of the implementation mode of the present application, based on the total weight of the first monomer, the second monomer and the third monomer as 100 parts, the weight fraction of the second monomer is within the above range. If it is lower than the weight fraction, the rheological properties will be weakened and the bonding strength will be reduced; if it is higher than the weight fraction, it will easily lead to an increase in the viscosity of the adhesive and even produce gel, affecting the processing of the adhesive.
[0040] In the technical solution of the implementation mode of the present application, based on the total weight of the first monomer, the second monomer and the third monomer as 100 parts, the weight fraction of the third monomer is within the above range. If it is lower than the weight fraction, the rheological properties will be weakened; if it is higher than the weight fraction, it will easily lead to insufficient viscosity of the binder, poor suspension ability of the electrode slurry, and affect the processing of the binder.
[0041] In the present application, there is no limitation on the functionality of isocyanate, for example, the functionality is ≥ 2, such as 3 or 4, etc., and difunctional isocyanate is further preferred.
[0042] In the present application, the functionality of isocyanate refers to the number of isocyanate groups (—N═C═O) contained in one isocyanate molecule that can participate in the reaction.
[0043] As an example, the isocyanate includes aliphatic isocyanate and / or aromatic isocyanate;
[0044] Among them, the aliphatic isocyanate includes any one of hexamethylene diisocyanate, trimethyl hexamethylene diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate, and lysine diisocyanate, or a combination of at least two thereof; the aromatic isocyanate includes any one of 4,4'-diphenylmethane diisocyanate, toluene diisocyanate, xylene diisocyanate, dimethylbiphenyl diisocyanate, p-phenylene diisocyanate, 1,5'-naphthalene diisocyanate, and 3,3'-dichlorobiphenyl-4,4'-diisocyanate, or a combination of at least two thereof.
[0045] In the present application, the added amount of the fourth monomer only needs to meet the preparation requirements. For example, based on the total molar amount of the first monomer, the second monomer and the third monomer as 100%, the molar amount of the fourth monomer is 100%-120%, for example, 112%, 114%, 116%, 118%, etc.
[0046] Preferably, the raw materials for preparing the binder also include a neutralizer.
[0047] In the technical solution of the embodiment of the present application, the raw materials for preparing the binder also include a neutralizer. The inventors have found that by neutralizing the carboxyl group of the second monomer, the polymer chain has a certain charge, which can further improve the rheological properties and thus further improve the quality of the electrode sheet.
[0048] Preferably, the neutralizing agent includes any one of alkali metal hydroxide, ammonia or organic amine, or a combination of at least two thereof.
[0049] As an example, the alkali metal hydroxide includes any one of lithium hydroxide, sodium hydroxide, and potassium hydroxide, or a combination of at least two of them; the organic amine includes any one of diethylamine, triethylamine, triethanolamine, N,N-dimethylethanolamine, N,N-diethylethanolamine, n-butanolamine, isobutanolamine, tetramethylammonium hydroxide, and tetramethylguanidine, or a combination of at least two of them.
[0050] In the present application, the amount of the neutralizer added only needs to meet the preparation requirements. For example, the weight of the neutralizer is not greater than the weight of the second monomer, that is, ≤30 parts, such as 5 parts, 10 parts, 15 parts, 20 parts, 25 parts, etc.
[0051] Preferably, the number average molecular weight of the binder is 50,000-200,000 g / mol, for example, 60,000 g / mol, 80,000 g / mol, 100,000 g / mol, 120,000 g / mol, 140,000 g / mol, 160,000 g / mol, 180,000 g / mol, etc.
[0052] In the technical solution of the implementation mode of the present application, the number average molecular weight of the binder is adjusted within the above range; the reason is that: the binder within the above number average molecular weight range is suitable for application in batteries; if the number average molecular weight of the binder is low, sedimentation behavior will occur during the subsequent preparation of battery slurry, resulting in poor uniformity of the coated electrode plates, affecting the performance of the battery; if the number average molecular weight is high, the prepared battery slurry is prone to local agglomeration, resulting in difficulty in dispersion, affecting the performance of the battery.
[0053] In the present application, in order to obtain a suitable number average molecular weight, a chain extender and / or terminator may be further added for adjustment.
[0054] Preferably, the number average molecular weight of the chain extender is lower than 600. For example, the chain extender includes any one of ethylene glycol, 1,2-propylene glycol, 1,4-butanediol, 1,4-butenediol, 1,5-pentanediol, neopentyl glycol, hexanediol, diethylene glycol, hydrazine, ethylenediamine, diethylenetriamine, triethylenetetramine, propylenediamine, butylenediamine, hexamethylenediamine, cyclohexanediamine, piperazine, 2-methylpiperazine, tris(2-aminoethyl)amine, and isophoronediamine, or a combination of at least two thereof.
[0055] Preferably, the number average molecular weight of the terminator is lower than 300. For example, the terminator includes any one of ethanol, butanol, dodecanol, phenol, dimethylamine, diethylamine, methylethylamine, dipropylamine, N-dodecylmethylamine, and N-methylaniline, or a combination of at least two thereof.
[0056] In a second aspect, the present application provides a method for preparing the binder according to the first aspect, the preparation method comprising the following steps:
[0057] The first monomer, the second monomer, the third monomer and the fourth monomer are mixed and reacted to obtain the binder.
[0058] Preferably, the preparation method comprises the following steps:
[0059] (1) mixing the first monomer and a portion of the fourth monomer to react to form a first oligomer solution;
[0060] (2) mixing the first oligomer solution obtained in step (1), the second monomer and a portion of the fourth monomer to form a second oligomer solution;
[0061] (3) The second oligomer solution obtained in step (2), the third monomer and the remaining fourth monomer are mixed and reacted to obtain the binder.
[0062] In the technical solution of the implementation mode of the present application, during the process of preparing the binder, the first monomer, the second monomer and the third monomer are added to the reaction system step by step, and the fourth monomer is added to the reaction system in batches, so that each functional monomer can form a polymer segment of a certain length, thereby improving the ability of the third monomer to form an ordered phase and the proportion of the ordered phase formed, thereby improving the rheological properties of the polymer.
[0063] Preferably, in step (1), the first monomer is first dispersed in a solvent.
[0064] Preferably, the solvent includes any one of N-methylpyrrolidone, N,N-dimethylacetamide, 3-methoxy-N,N-dimethylpropionamide, 5-(dimethylamino)-2-methyl-5-oxo-pentanoic acid methyl ester, or a combination of at least two thereof.
[0065] Preferably, based on the total mass of the fourth monomer in steps (1), (2) and (3) being 100%, the mass of the portion of the fourth monomer in step (1) is 10%-40%, for example 15%, 20%, 25%, 30%, 35%, etc.
[0066] Preferably, in step (1), the temperature of the mixed reaction is 60-100°C, such as 70°C, 80°C, 90°C, etc.; and / or;
[0067] The mixing reaction time is 0.1-10 h, for example, 1 h, 2 h, 4 h, 6 h, 8 h, etc.
[0068] Preferably, based on the total mass of the fourth monomer in steps (1), (2) and (3) as 100%, the mass of the portion of the fourth monomer in step (2) is 30%-80%, for example 35%, 40%, 50%, 60%, 70%, etc.
[0069] Preferably, in step (2), the temperature of the mixed reaction is 60-100°C, such as 70°C, 80°C, 90°C, etc.; and / or;
[0070] The mixing reaction time is 0.1-10 h, for example, 1 h, 2 h, 4 h, 6 h, 8 h, etc.
[0071] Preferably, in step (3), the temperature of the mixed reaction is 60-100°C, such as 70°C, 80°C, 90°C, etc.; and / or;
[0072] The mixing reaction time is 0.1-10 h, for example, 1 h, 2 h, 4 h, 6 h, 8 h, etc.
[0073] Preferably, in step (3), after the mixing reaction, the step further includes adding a neutralizing agent.
[0074] As a preferred technical solution, the preparation method comprises the following steps:
[0075] (1) dissolving the first monomer in a solvent, adding a portion of the fourth monomer, heating to 60-100° C., stirring and mixing to react for 0.1-10 hours until no bubbles are generated, thereby forming a first oligomer solution;
[0076] (2) adding the second monomer and part of the fourth monomer (30%-50% of the total mass of the fourth monomer) to the first oligomer solution, heating to 60-100° C., stirring and mixing for 0.1-10 hours, to form a second oligomer solution;
[0077] (3) Add the third monomer and the remaining fourth monomer (20%-40% of the total mass of the fourth monomer) to the second oligomer solution, heat to 60-100° C., stir and mix to react for 0.1-10 h, and obtain the binder.
[0078] In a third aspect, the present application provides an electrode slurry, comprising the binder described in the first aspect, or the binder obtained by the preparation method described in the second aspect;
[0079] As an example, the electrode slurry of the present application may be a positive electrode slurry or a negative electrode slurry.
[0080] In the present application, the electrode slurry includes an active material, a binder, a conductive agent and a solvent.
[0081] The present application does not limit the composition of the electrode slurry, and any material known in the art may be used.
[0082] As an example, the solid content of the electrode slurry may be 50%-80%, such as 55%, 60%, 65%, 70%, 75%, etc.
[0083] As an example, the mass ratio of active material, binder and conductive agent can be (92-99): (0.5-4): (0.5-4), wherein 92-99 can be 93, 94, 95, 96, 97, 98, etc.; 0.5-4 can be 1, 1.5, 2, 2.5, 3, 3.5, etc.; the added amounts of binder and conductive agent can be the same or different.
[0084] As an example, taking the positive electrode slurry as an example, the active material therein can be selected from phosphate materials such as lithium iron phosphate, etc.; the conductive agent can be selected from zero-dimensional conductive agent (such as carbon black, etc.), one-dimensional conductive agent (such as carbon nanotubes, etc.), two-dimensional conductive agent (such as graphene, etc.) or three-dimensional conductive agent (such as porous carbon, etc.); the solvent can be selected from N-methylpyrrolidone, etc.
[0085] In a fourth aspect, the present application provides an electrode plate, which includes the binder described in the first aspect, or the binder obtained by the preparation method described in the second aspect, or the electrode slurry described in the third aspect.
[0086] As an example, the electrode plate of the present application may be a positive electrode plate or a negative electrode plate.
[0087] In the present application, the electrode plate includes a current collector and an active material layer disposed on at least one surface of the current collector;
[0088] The active material layer includes the binder described in the first aspect, or the binder obtained by the preparation method described in the second aspect, or the electrode slurry described in the third aspect.
[0089] The present application does not limit the structure and composition of the electrode sheet, and any structure or material known in the art may be used. As an example, the current collector may be a positive electrode current collector, such as aluminum foil, or a negative electrode current collector, such as copper foil.
[0090] Taking the positive electrode sheet as an example, the preparation method of the electrode sheet described in the present application includes the following steps:
[0091] Active material layer materials, such as active materials (such as lithium iron phosphate, etc.), binders and conductive agents (such as carbon black, etc.) are dissolved in a solvent (such as N-methylpyrrolidone, etc.) according to a formula to form a positive electrode slurry, and then the positive electrode slurry is coated on the surface of a current collector (such as aluminum foil, etc.), and the positive electrode sheet is obtained through operations such as drying and pressing.
[0092] In a fifth aspect, the present application provides a battery, comprising the binder described in the first aspect, or the binder obtained by the preparation method described in the second aspect, or the electrode slurry described in the third aspect, or the electrode plate described in the fourth aspect.
[0093] Compared with the prior art, this application has at least the following beneficial effects:
[0094] (1) The binder described in the present application not only has excellent bonding properties, but also improves the rheological properties of the electrode slurry formed by it, and improves the coating and processing performance of the electrode slurry; further, the edge flatness of the electrode plate formed is high, and the binder improves the quality of the electrode plate, so that a battery with excellent comprehensive performance can be obtained.
[0095] (2) The electrode slurry formed by the binder described in this application has a shear rate of 1s -1 , viscosity in the range of 10290-19220 mPa·s, shear rate of 100 s -1, the viscosity is in the range of 3840-8250mPa·s, and the recovery time is in the range of 14-39s; the electrode sheet formed by the binder, the peel strength of the active material layer and the current collector is 69N·m -1 Above, the edge flatness of the electrode plate is within ±12%.
[0096] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. DETAILED DESCRIPTION
[0097] The following is a detailed description of the embodiments of the technical solution of the present application. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0098] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the description and claims of this application and any variations thereof are intended to cover non-exclusive inclusions.
[0099] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0100] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0101] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following ranges can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "2-10" means that all real numbers between "2-10" are listed in this document, and "2-10" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0102] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists, A and B exist at the same time, and B exists. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0103] In this application, the raw material information involved in each embodiment is as follows:
[0104] 3,3',4,4'-Biphenyltetracarboxylic dianhydride: purchased from Tianjin Zotye;
[0105] 3,4'-Diaminodiphenyl ether: purchased from Tianjin Zotye;
[0106] 1,3-Bis(3-aminopropyl)tetramethyldisiloxane: purchased from Shanghai MacLean;
[0107] Lysine: purchased from Shanghai Yuanye Biotechnology;
[0108] 4,4'-Diamino-3,3'-dicarboxyl-5,5'-dimethylbiphenyl: purchased from Shanghai MacLean;
[0109] Bis(4-amino-3,5-dicarboxyphenyl) ether: purchased from Shanghai MacLean;
[0110] Polyamide diol: purchased from Lubrizol, brand name Aptalon TM 9501, number average molecular weight 2250 g / mol;
[0111] Polyester diamine: polyethylene succinate diamine, purchased from Evonik, Germany, brand VERSALINK P1000, number average molecular weight 1200 g / mol;
[0112] Polyether diol: purchased from Jiangsu Hai'an Petrochemical Plant, model N210, molecular weight 1000 g / mol;
[0113] Decanediol: purchased from Shanghai McLean;
[0114] N-Methylpyrrolidone: purchased from Maiqi Chemical;
[0115] N,N-dimethylacetamide: purchased from Shanghai MacLean;
[0116] 5-(Dimethylamino)-2-methyl-5-oxo-pentanoic acid methyl ester: purchased from Solvay, Belgium.
[0117] Example 1
[0118] This embodiment provides a binder, and the raw materials for preparing the binder include the following components:
[0119] First monomer: 20 parts by weight, 3,3',4,4'-biphenyltetracarboxylic dianhydride;
[0120] Second monomer: 30 parts by weight, lysine;
[0121] The third monomer: 50 parts by weight, polyamide diol, number average molecular weight 2250 g / mol;
[0122] Fourth monomer: 54 parts by weight, toluene diisocyanate;
[0123] Solvent: 120 parts by weight, N-methylpyrrolidone.
[0124] The binder is obtained by the following preparation method, which comprises the following steps:
[0125] (1) dissolving 3,3',4,4'-biphenyltetracarboxylic acid dianhydride (20 parts by weight) in (120 parts by weight) N-methylpyrrolidone, adding toluene diisocyanate (13 parts by weight), heating to 80° C. and stirring the mixture for 3 hours until no bubbles are generated, thereby forming a first oligomer solution;
[0126] (2) adding lysine (30 parts by weight) and toluene diisocyanate (36 parts by weight) to the first oligomer solution, heating to 100° C. and stirring the mixture for 4 hours to form a second oligomer solution;
[0127] (3) Adding polyamide diol (50 parts by weight) and toluene diisocyanate (5 parts by weight) to the second oligomer solution, heating to 80° C. and stirring and mixing for 2 hours to obtain the binder.
[0128] Examples 2-12 and Comparative Examples 1-2
[0129] Except for the parameters in Tables 1-3, the binder was obtained according to the preparation method described in Example 1.
[0130] Table 1
[0131]
[0132]
[0133] Table 2
[0134]
[0135]
[0136] Table 3
[0137]
[0138]
[0139] In the table, “—” refers to data not involved.
[0140] In Examples 2 and 3, the neutralizing agent is added after the mixing reaction in step (3).
[0141] In Example 11, the neutralizing agent is added after the mixing reaction in step (3), and the rest is the same as in Example 1.
[0142] Example 13
[0143] The difference between this embodiment and embodiment 1 is that the first monomer, the second monomer, the third monomer and the fourth monomer are directly mixed, heated to 80° C., stirred and mixed for reaction for 9 hours to obtain a binder.
[0144] 1. Test of electrode slurry:
[0145] (1) Preparation of electrode slurry
[0146] In parts by weight, 95 parts of lithium iron phosphate (Hunan Yuneng, model Y9), 2.5 parts of conductive carbon black Super P and 2.5 parts of binder were added to N-methylpyrrolidone at a ratio of 65% of the total solid content, and fully mixed using a double planetary mixer to obtain an electrode slurry containing the prepared binder.
[0147] (2) Viscosity of electrode slurry: The viscosity of electrode slurry was tested using a rotational rheometer at 25°C. The shear rate in the first stage was set to 1s -1 , the rotation time is 30s, the viscosity data is collected once per second, and the viscosity at the 30th second is recorded as η1; the shear rate of the second stage is set to 100s -1 , the rotation time is 5s, the viscosity data is collected every 0.5 seconds, and the viscosity of the 5th second is recorded as η2; the shear rate of the third stage is set to 1s -1 , the rotation time is 200s, the viscosity data is collected once per second, and when the viscosity recovers to 85% of η1, the recovery time is recorded as t.
[0148] The test results are summarized in Table 4.
[0149] Table 4
[0150]
[0151] According to the data in Table 4, the electrode slurry formed by the binder described in this application has a shear rate of 1s -1 , viscosity in the range of 10290-19220 mPa·s, shear rate of 100 s -1 , the viscosity is in the range of 3840-8250 mPa·s, and the recovery time is in the range of 14-39 s; the binder described in the present application improves the rheological properties of the electrode slurry formed therefrom and improves the coating processing performance of the electrode slurry.
[0152] Taking Examples 1-3 and Example 11 as examples, within the preferred range, the recovery time of the electrode slurry formed by the binder described in the present application is in the range of 18-20 seconds.
[0153] Analysis of Comparative Examples 1-2 and Example 1 shows that the binder of Comparative Example 1 does not contain a small molecule carboxyl polyamine structure, and the binder of Comparative Example 2 does not contain a polymer polyamine or polymer polyol structure. The thixotropy of the electrode slurry prepared in this way is significantly reduced, and the slurry viscosity recovery time is significantly increased, which proves that the inclusion of the second monomer and the third monomer in the preparation raw materials of the binder is more conducive to improving the performance of the electrode slurry.
[0154] Analysis of Example 4 and Example 1 shows that the thixotropy of the electrode slurry prepared in Example 4 is lower than that in Example 1, and the slurry viscosity recovery time is increased, which proves that among the third monomers of the binder, the polymer polyamine is preferably polyamide polyamine, polyester polyamine, polyesteramide polyamine or polyacetal polyamine; the polymer polyol is preferably polyamide polyol, polyester polyol, polyesteramide polyol or polyacetal polyol, which is more conducive to improving the performance of the electrode slurry.
[0155] Analysis of Examples 5-10 and Example 1 shows that the edge flatness and other properties of the electrode sheets of Examples 5-10 are not as good as those of Example 1, proving that based on the total mass of the first monomer, the second monomer and the third monomer as 100 parts, the first monomer, the second monomer and the third monomer are within the preferred range of the present application, which is more conducive to improving the performance of the electrode slurry.
[0156] Analysis of Example 11 and Example 1 shows that the performance of Example 11 is better than that of Example 1, which proves that adding a neutralizing agent to the raw materials for preparing the binder is more conducive to improving the performance of the electrode slurry.
[0157] Analysis of Example 12 and Example 1 shows that the performance of Example 12 is not as good as that of Example 1, proving that the polymer polyol is preferably polyamide polyol, polyester polyol, polyesteramide polyol or polyacetal polyol, which is more conducive to improving the performance of the electrode slurry. Similarly, the polymer diamine is preferably polyamide diamine, polyester diamine, polyesteramide diamine or polyacetal diamine, which is more conducive to improving the performance of the electrode slurry.
[0158] Analysis of Example 13 and Example 1 shows that the performance of Example 13 is not as good as that of Example 1, which proves that adding the various raw materials of the binder in batches or in sequence is more conducive to improving the performance of the electrode slurry.
[0159] 2. Test of electrode plates
[0160] (1) Preparation of electrode sheets
[0161] The electrode slurry was filtered through a 100-mesh screen and then coated on a 10 μm thick aluminum foil at a speed of 40 m / min by an extrusion coater to form an active material layer. After drying in a forced air drying oven at 110 °C, the active material layer was coated at 1 × 10 4 The electrode sheet is obtained by rolling with a unit length load of N / m.
[0162] (2) Edge flatness of the electrode plate: The edge thickness of the electrode plate is measured as h1; the average thickness of the electrode plate is measured as h2; and the edge flatness is calculated as (h1-h2) / h2×100%.
[0163] (3) Peel strength of active material layer in electrode sheet: The electrode sheet prepared as above was cut into strips of 100 mm × 20 mm. The current collector side was fixed to a steel plate with a thickness of 1 mm using double-sided tape. A transparent tape was pasted on the coating layer side. A 180° pulling peeling test was performed at a peeling speed of 100 mm / min using a universal electronic testing machine at 25°C, and the peeling strength was recorded.
[0164] The test results are summarized in Table 5.
[0165] Table 5
[0166]
[0167]
[0168] According to the data in Table 5, the peel strength of the electrode sheet, active material layer and current collector formed by the binder described in this application is 69N·m -1 As mentioned above, the edge flatness of the electrode plate is within ±12%; the binder described in the present application improves the rheological properties of the electrode slurry formed thereby on the basis of having excellent bonding properties, and improves the coating and processing properties of the electrode slurry; further, the edge flatness of the electrode plate formed is high, and the binder improves the quality of the electrode plate, so that a battery with excellent comprehensive performance can be obtained.
[0169] Taking Examples 1-3 and Example 11 as examples, within the preferred range, the electrode slurry formed by the binder described in the present application has an edge flatness within the range of ±3%.
[0170] Analysis of Comparative Examples 1-2 and Example 1 shows that the performance of Comparative Examples 1-2 is not as good as that of Example 1, which proves that the inclusion of the second monomer and the third monomer in the raw materials for preparing the binder is more conducive to improving the performance of the electrode plate.
[0171] Analysis of Example 4, Comparative Example 3 and Example 1 shows that the performance of Example 4 and Comparative Example 3 is not as good as that of Example 1, which proves that among the third monomers of the binder, the polymer polyamine is preferably polyamide polyamine, polyester polyamine, polyesteramide polyamine or polyacetal polyamine; the polymer polyol is preferably polyamide polyol, polyester polyol, polyesteramide polyol or polyacetal polyol, which is more conducive to improving the performance of the electrode plate.
[0172] Analysis of Examples 5-10 and Example 1 shows that the performance of Examples 5-10 is not as good as that of Example 1, which proves that based on the total mass of the first monomer, the second monomer and the third monomer as 100 parts, the first monomer, the second monomer and the third monomer are within the preferred range of the present application, which is more conducive to improving the performance of the electrode plate.
[0173] Analysis of Example 11 and Example 1 shows that the performance of Example 11 is better than that of Example 1, which proves that adding a neutralizing agent to the raw materials for preparing the binder is more conducive to improving the performance of the electrode plate.
[0174] Analysis of Example 12 and Example 1 shows that the performance of Example 12 is not as good as that of Example 1, which proves that the polymer polyol is preferably polyamide polyol, polyester polyol, polyesteramide polyol or polyacetal polyol, which is more conducive to improving the performance of the electrode plate. Similarly, the polymer diamine is preferably polyamide diamine, polyester diamine, polyesteramide diamine or polyacetal diamine, which is more conducive to improving the performance of the electrode plate.
[0175] Analysis of Example 13 and Example 1 shows that the performance of Example 13 is not as good as that of Example 1, which proves that adding the various raw materials of the binder in batches or in sequence is more conducive to improving the performance of the electrode plate.
[0176] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them; although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.
Claims
1. A binder, characterized in that: The raw materials for preparing the binder include a first monomer, a second monomer, a third monomer and a fourth monomer; The first monomer includes a cyclic anhydride compound and / or a non-carboxyl polyamine; The second monomer includes a small molecule carboxyl polyamine; The third monomer includes a polymer polyamine and / or a polymer polyol; The fourth monomer includes isocyanate.
2. The adhesive according to claim 1, characterized in that The cyclic acid anhydride compounds include 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,3,3',4'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride, 2,3,3',4'-diphenyl ether tetracarboxylic dianhydride, 4,4'-(4,4'-isopropyldiphenoxy)bis(phthalic anhydride), 3,3',4,4'-diphenyl sulfone tetracarboxylic dianhydride, p-phenylene dicarboxylic dianhydride, Any one of (trimellitic acid ester) dianhydride, 1,2,4-benzenetricarboxylic anhydride, cyclopentanetetracarboxylic anhydride, pyromellitic anhydride, tetrahydropyromellitic anhydride, 1,2,4-cyclohexanetricarboxylic anhydride, 1,4,5,8-naphthalenetetracarboxylic anhydride, 1,2,3,4-cyclobutanetetracarboxylic anhydride, and bicyclo(2.2.2)oct-7-ene-2,3,5,6-tetracarboxylic anhydride, or a combination of at least two thereof; Preferably, the cyclic anhydride compound includes any one of 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride, 2,3,3',4'-diphenyl ether tetracarboxylic dianhydride or 4,4'-(4,4'-isopropyldiphenoxy)bis(phthalic anhydride) or a combination of at least two thereof; Preferably, the number of amino groups in the non-carboxyl polyamine is ≥2, and optionally, the non-carboxyl polyamine includes a non-carboxyl diamine; Preferably, the non-carboxyl polyamine includes p-phenylenediamine, m-phenylenediamine, 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 4,4'-diaminobenzophenone, 2,7-diamino-9-fluorenone, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminodiphenyl sulfone, 4,4'-diaminobiphenyl, 4,4'-diaminodiphenylmethane, 1,4-bis(4'-aminophenoxy)benzene, 1,3-bis(4'-aminophenoxy)benzene, 2,2- Any one of bis[4-(4-aminophenoxy)phenyl]propane, 2,2'-bis(trifluoromethyl)diaminobiphenyl, 5-amino-2-(4-aminophenyl)benzimidazole, 1,2-bis(2-aminoethoxy)ethane, 3,6,9-trioxaundecane-1,11-diamine, 3,6,9,12-tetraoxatetradecane-1,14-diamine, polyoxyethylene diamine, and 1,3-bis(3-aminopropyl)tetramethyldisiloxane, or a combination of at least two thereof; Preferably, the non-carboxyl polyamine includes one or a combination of two or more of 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 1,4-bis(4'-aminophenoxy)benzene, 1,3-bis(4'-aminophenoxy)benzene, 2,2-bis[4-(4-aminophenoxy)benzene]propane, 1,2-bis(2-aminoethoxy)ethane, 3,6,9-trioxaundecane-1,11-diamine, 3,6,9,12-tetraoxatetradecane-1,14-diamine, polyoxyethylene diamine, and 1,3-bis(3-aminopropyl)tetramethyldisiloxane.
3. The adhesive according to claim 1 or 2, characterized in that: The number of amino groups in the small molecule carboxyl polyamine is ≥ 2, and optionally, the small molecule carboxyl polyamine includes a small molecule carboxyl diamine; Preferably, the small molecule carboxyl polyamine includes lysine, hydroxylysine, arginine, histidine, 2,5-diaminocyclohexanecarboxylic acid, 3,5-diaminocyclohexanecarboxylic acid, 2,4-diaminobenzoic acid, 2,5-diaminobenzoic acid, 3,5-diaminobenzoic acid, 4,6-diamino-1,3-phthalic acid, 2,5-diamino-1,4-phthalic acid, 4,4'-diaminobiphenyl-3-carboxylic acid, 4,4'-diaminobiphenyl-3,3'-dicarboxylic acid, 4,4'-diaminobiphenyl-2,2'-dicarboxylic acid, 3,3'-diaminobiphenyl-4,4'-dicarboxylic acid, 3,3'-diaminobiphenyl-2,4'-dicarboxylic acid, 4,4'-diamino-3,3'-dicarboxy-5,5'-dimethylbiphenyl, 4,4'-diamino-3,3'-dicarboxylic acid Any one or a combination of at least two of -5,5'-dimethoxybiphenyl, 4,4'-diaminodiphenylmethane-3-carboxylic acid, 4,4'-diaminodiphenylmethane-3,3'-dicarboxylic acid, 4,4'-diaminodiphenylethane-3-carboxylic acid, 4,4'-diaminodiphenylethane-3,3'-dicarboxylic acid, bis(4-amino-3-carboxyphenyl) ether, bis(4-amino-3,5-dicarboxyphenyl) ether, 1,4-bis(4-amino-3-carboxyphenoxy)benzene, 1,3-bis(4-amino-3-carboxyphenoxy)benzene, bis(4-amino-3-carboxyphenyl) sulfone, bis(4-amino-3,5-dicarboxyphenyl) sulfone, bis[4-(4-amino-3-carboxyphenoxy)phenyl]sulfone, and bis[4-(4-amino-3-carboxyphenoxy)phenyl]propane.
4. The adhesive according to any one of claims 1 to 3, characterized in that: The number average molecular weight of the third monomer is ≤3000 g / mol; Preferably, the number of amino groups in the polymer polyamine is ≥2, and optionally, the polymer polyamine includes a polymer diamine; Preferably, the polymer polyamine includes any one or a combination of at least two of polyamide polyamine, polyester polyamine, polyesteramide polyamine or polyacetal polyamine; Preferably, the polymer diamine includes any one or a combination of at least two of polyamide diamine, polyester diamine, polyester amide diamine or polyacetal diamine; Preferably, the number of hydroxyl groups in the polymer polyol is ≥ 2, and optionally, the polymer polyol comprises a polymer diol; Preferably, the polymer polyol comprises any one or a combination of at least two of polyamide polyol, polyester polyol, polyesteramide polyol or polyacetal polyol; Preferably, the polymer diol includes any one of polyamide diol, polyester diol, polyesteramide diol or polyacetal diol, or a combination of at least two thereof.
5. The adhesive according to any one of claims 1 to 4, characterized in that: Based on 100 parts by weight of the total weight of the first monomer, the second monomer and the third monomer, the weight of the first monomer is 20 to 40 parts; and / or; The weight proportion of the second monomer is 10 to 30 parts; and / or; The weight proportion of the third monomer is 30 to 70 parts; Preferably, the raw materials for preparing the binder further include a neutralizing agent; Preferably, the neutralizing agent comprises any one or a combination of at least two of alkali metal hydroxide, ammonia or organic amine; Preferably, the number average molecular weight of the binder is 50,000-200,000 g / mol.
6. A method for preparing the binder according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: The first monomer, the second monomer, the third monomer and the fourth monomer are mixed and reacted to obtain the binder.
7. The preparation method according to claim 6, characterized in that: The preparation method comprises the following steps: (1) mixing the first monomer and a portion of the fourth monomer to react to form a first oligomer solution; (2) mixing the first oligomer solution obtained in step (1), the second monomer and a portion of the fourth monomer to form a second oligomer solution; (3) mixing the second oligomer solution obtained in step (2), the third monomer and the remaining fourth monomer to obtain the binder; Preferably, in step (1), the first monomer is first dispersed in a solvent; Preferably, the solvent includes any one of N-methylpyrrolidone, N,N-dimethylacetamide, 3-methoxy-N,N-dimethylpropionamide, 5-(dimethylamino)-2-methyl-5-oxo-pentanoic acid methyl ester or a combination of at least two thereof; Preferably, based on the total mass of the fourth monomer in steps (1), (2) and (3) being 100%, the mass of the portion of the fourth monomer in step (1) is 10%-40%; Preferably, based on the total mass of the fourth monomer in steps (1), (2) and (3) being 100%, the mass of the portion of the fourth monomer in step (2) is 30%-80%; Preferably, in step (3), after the mixing reaction, the step further includes adding a neutralizing agent.
8. An electrode slurry, characterized in that: The invention comprises the binder according to any one of claims 1 to 5, or the binder obtained by the preparation method according to claim 6 or 7.
9. An electrode plate, characterized in that: The electrode plate comprises the binder according to any one of claims 1 to 5, or the binder obtained by the preparation method according to claim 6 or 7, or the electrode slurry according to claim 8.
10. A battery, characterized in that: The battery comprises the binder according to any one of claims 1 to 5, or the binder obtained by the preparation method according to claim 6 or 7, or the electrode slurry according to claim 8, or the electrode plate according to claim 9.
Citation Information
Patent Citations
Binder for electrodes of lithium secondary batteries, and lithium secondary battery which uses electrode produced using binder for electrodes of lithium secondary batteries
CN104115316A
Self-adhesive label containing biodegradable waterborne polyurethane pressure-sensitive adhesive
CN116897197A
Hydrophilic polymer, method of producing the same, and binder and electrode prepared therewith
JP2016121317A
Cited By
Binder, preparation method therefor and use thereof
WO2026138338A1